Evaluation of Drivers and Barriers of Wind Power Generation in Pakistan. SWOT-Delphi Method - Bhutto, Zuhaibuddin; Abbasi, Sikandar Ali; Jamali, Saeed Zaman; Masroor, Salman; Shah, Jalal; Shaikh, Murtaza Hussain; Hussain, Ayaz (International Journal of Energy Economics and Policy, 2022)
In the last two decades electricity shortage has hampered the economic growth of Pakistan. To overcome these crises, thermal power plants were commissioned to bridge the supply and demand gap. Deployment of thermal power generation resulted in an unsustainable energy mix with the higher cost of generation. In the last decade, policymakers have shown considerable interest in deploying renewable energy generally and wind energy particularly. Therefore, this paper evaluates some important drivers and barriers to wind power generation. SWOT-Delphi approach with Relative Importance Index (RII) analysis has been applied. The results show that the deployment of wind power can enhance energy security and environmental sustainability. Major barriers to wind energy are the presence of competitive energy resources, policy implications, and poor grid infrastructure. With this contrasting environment, the evaluation of drivers and barriers of wind power are insightful for formulating sustainable energy planning strategies for future generation mix.